THE PREVALENCE OF HYPERTHYROIDISM AT UNIVERSITY OF MAIDUGURI TEACHING HOSPITAL (UMTH), MAIDUGURI - Tahir MB; Kolawole A; Bakari AA; Suleiman A; Mubi B (Ntec Specialist, 2014)
Background: Hyperthyroidism and hypothyroidism are the two common thyroid disorders but there is paucity of information on the prevalence of hyperthyroidism in Nigeria in general and in Northeast of Nigeria in particular. Objective: To determine the prevalence of hyperthyroidism at University of Maiduguri Teaching Hospital. Method: A retrospective study done over a period of one year that reviews the results of serum TSH, T3 and T4 from 203 patients. Results: Eighty-nine (43.8%) and 79 (38.9%) patients had elevated serum levels of T3 and T4 respectively (i.e. were hyperthyroid), 114 (56.2%) and 112 (55.2%) patients had normal serum levels of T3 and T4 respectively (i.e. were euthyroid) while 12 (5.9%) patients had low serum levels of T4 only (i.e. were hypothyroid). The female to male ratio of hyperthyroidism was 4 and 1 [T3 - female 68 (35.4%), male - 17(89%); T4 - female 59(30.7%), male 15(7.8%)]. Age-group from 25-34 years was the most frequent (51 patients) and with the highest prevalence of hyperthyroidism [T3 - 19(14.2%); T4 18(13.4%)]. The study further revealed a decline in the prevalence of hyperthyroidism as age increased. The finding of high prevalence of low TSH (20.8%) against high prevalence of elevated T3 and T4 [89(44.1% and 79(38.9%) respectively] in this study could suggest that the hyperthyroidism in the studied patients could have been largely caused by Graves' disease. Conclusion: This study revealed that thyroid disorders are not uncommon in our environment and the finding of high prevalence of low TSH above high TSH, suggested that the hyperthyroidism discovered in our study may have been largely caused by Grave's disease. We recommend that more laboratory diagnostic centre should be established in our environment where thyroid disorders can be diagnosed